Preparation and Removal Properties of Zinc Treated Fe(0)/Graphene for Methylene Blue - Qin, Zhong-Qiong (Asian Journal of Chemistry, 2014)
Graphene oxide as the precursor, zinc treated zero valent iron (Fe(0))/graphene functional composite materials were prepared by using wet chemical reduction method. The impact of different iron salts and zinc salts on the surface of graphene was investigated. The structure and morphology of functional composite was studied. The composition and structure of the zinc treated Fe(0)/graphene composite was compared and analyzed using XRD, SEM and a combination of different experimental conditions on the decolorization and enrichment separation performance of methylene blue. The rules of zinc treated Fe(0)/graphene composites on the decolorization of methylene blue were explored and its stability and magnetic changes were also analyzed.